Warm Climate Production Guidelines for Japanese Hydrangeas: ENH910/EP177, 2/2005 - Shoellhorn, Rick; Richardson, Alexis A. (EDIS, 2005)
Lace cap hydrangeas can be a great way for Florida growers to produce something that defines their niche as specialty growers and offers a high profit plant for spring and holiday sales. This document is ENH910, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date February 5, 2005.